The current status of the case report: terminal or viable - Abu Kasim, N.H.; Abdullah, B.J.; Manikam, J. (2009)
The case report, which has a long history in medicine, has seen its fortune wax and wane with time. We discuss the challenges facing the continued survival of the case report, including the inability of journals to cope with the increased load and increased cost of publication, ethical issues, the impact factor and the rise of evidence-based medicine. We highlight the important role that the case report will continue to play in medical research and education, as a means of sharing information and detecting novelty through observations. Most importantly, the case report serves as a stepping stone for young physicians and practitioners into the world of medical writing.